OSOBOWE ŹRÓDŁA INFORMACJI JAKO JEDNA Z METOD OPERACYJNEGO DZIAŁANIA ORGANÓW POLICYJNYCH - Teluk, Rafał (Zeszyty Prawnicze, 2016)
INDIVIDIDUAL PERSONS AS SOURCES OF INFORMATION: AN OPERATIONAL METHOD USED BY POLICE FORCES Summary The aim of this article is to discuss an important issue in criminalistics, the use of information acquired from individuals in the police’s operational and investigative work. The author presents the methods and aims of the activities pursued out of court by authorised agencies of the state. He discusses the problems involved in the collection and recording of information from individuals who collaborate with the police, the influence this type of information has on the collection of evidence, and its value in court proceedings. Another issue discussed in the article is the institution of the secret police agent – probably the police’s oldest, classical source of confidential information. The article also addresses the question of the protection and remuneration of police informers.